Perspektivy ispol'zovaniya ekstrakta solodki goloi v sportivnoi praktike - Belyaev, N. G.; Baturin, V. A.; Solgalov, G. D.; Kuzmenko, O. V. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The modern sport are described by the substantial growth of the volume and the intensity of training process that creates big loading on the adaptable potential of an organism of the training person. Therefore during the training and the restoration the help in the management of physiological and biochemical reactions is necessary for an organism of the athlete. In this connection quite explainable is the heightened interest to the use of the resources normalizing and accelerating the regenerative processes, but not concerning to drugs. In this case the use of the adaptogenes of the vegetative and the animal origin is very perspective. Thus, from the research data becomes obvious, that the application of an liquorice naked extract promotes the integrative increase of the reserves of the functioning of organs and systems which determining physical and intellectual preparedness of an organism that opens ample opportunities for the use of this pharmacy for training of athletes in various kinds of sports.